Pengaruh Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Bengkel Mobil Paramitha Auto Graha (PAG) Denpasar - Shastri, Ambika; Pramudana, Komang Agus Satria (E-Jurnal Manajemen; Vol 3 No 2 (2014), 2014)
Service quality is an important thing to consider in order to maintain the existence of the company. With the good service quality then customer satisfaction can be achieved. The intention of this study was to determine the effect of the quality of services consisting of tangible, reliability, responsiveness, assurance, and empathy simultaneously and partially on customer satisfaction in Paramitha Auto Graha (PAG) car workshop. The research was took place in Paramitha Auto Graha (PAG) car workshop located at Jl. Ahmad Yani Utara 999, Denpasar. This study using 115 respondents were selected by accidental sampling technique, and using multiple linear regression data analysis techniques. The results indicate that the service quality consisting of physical evidence, reliability, responsiveness, assurance, and empathy simultaneously and partially had positive and significant impact on customer satisfaction Paramitha Auto Graha (PAG) car workshop. Keywords: service quality and customer satisfaction
Keywords: service quality and customer satisfaction